Etude des mortalités ostréicoles de l'hiver 1998/1999 en Baie des Veys. Caractérisation et analyse temporelle des dessalures observées sur les parcs conchylicoles de la baie de Veys depuis 1996. - Ropert, Michel; Kopp, Joel (2000)
The Shellfish Laboratory of Normandy (LCN : Laboratoire Conchylicole de Normandie) observed unusual hydrologic anomalies associated with important oyster mortalities during the winter of 1999. These anomalies were described as sudden salinity variations during the lidal cycle, particularly on the rising tide. Starting in 1996 a multi-parameter probe was used to monitor salinity, temperature and depth every 10 to 20 minutes in the inter-tidal zone. Alter data processing and filtering, two criteria concerning low salinity were chosen : amplitude and duration. Application of a cumulative function (Ibanez et al., 1993) to this time series data treatment showed the 3 year trend (1996-1999). Salinity variation data and climatic data were used in a multivariate analysis to determine the processes inducing low salinity events. This study demonstrated the occurrence of an annual cycle characterised by high variation in salinity during 2 months in winter and low variation during the other months. However, 1998 and 1999 were characterised by longer periods of low salinity (5 months in 1999) and an overall higher variability in salinity concentrations. These anomalies were strongly correlated to westerly winds coupled with high rainfall for 5 days prior to measurement. To explain these recent low salinity events, ail these phenomena were considered within the context of the dynamic environment of the entire bay. Dans le cadre de l'étude des mortalités ostréicoles importantes (20 à 30 %), qui ont frappé la Baie des Veys (Baie de Seine Occidentale) durant l'hiver 1998/1999, le Laboratoire Conchylicole de Normandie (LCN IFREMER) a pu mettre en évidence de fortes anomalies hydrologiques durant cette période. Ces anomalies se traduisaient par de brutales variations de salinité au cours du cycle de marée, en particulier en début de flot. Les mesures de terrain ont été réalisées au moyen d'une sonde multiparamétrique (salinité, température, pression) placée sur le terrain en continu depuis 1996 (fréquence d'acquisition : 10 à 20 ...